Repeated Nitrous Oxide Exposure Exerts Antidepressant-Like Effects Through Neuronal Nitric Oxide Synthase Activation in the Medial Prefrontal Cortex - Liu, Wei; Li, Qian; Ye, Binglu; Cao, Hang; Shen, Fuyi; Xu, Zhendong; Du, Weijia; Guo, Fei; Liu, Jinqi; Li, Tianyu; Zhang, Bing; Liu, Zhiqiang (Frontiers in Psychiatry, 2020)
Clinical studies have demonstrated that exposure to the inhalational general anesthetic nitrous oxide (N2O) produces antidepressant effects in depressed patients. However, the mechanisms underlying the antidepressant effects of N2O remain largely unknown. Neuronal nitric oxide synthase (nNOS) – mediated nitric oxide (NO) synthesis is essential for brain function and underlies the molecular mechanisms of many neuromodulators. We hypothesized that activation of the nNOS/NO pathway in the medial prefrontal cortex (mPFC) might mediate the antidepressant effects of N2O. In this study, we revealed that repeated N2O exposure produced antidepressant-like responses in mice. Our mechanistic exploration showed that repeated N2O exposure increased burst firing activity and that the expression levels of BDNF with nNOS activation were dependent in the mPFC. In particular, the antidepressant-like effects of N2O were also antagonized by local nNOS inhibition in the mPFC. In summary, our results indicated that N2O exposure enhances BDNF expression levels and burst firing rates in an nNOS activation dependent manner, which might underlie the pharmacological mechanism of the antidepressant-like effects of N2O exposure. The present study appears to provide further mechanistic evidence supporting the antidepressant effects of N2O.